biomedicalresearch 2019
DOI: 10.35841/biomedicalresearch.30-19-840
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker in insulin resistant and its complication.

Abstract: Aims: In Type 2 diabetes, Insulin resistant leads microvascular and macrovascular complication. Early finding prevents from this complication and it is a challenging task. A decade research shows adiponectin may be a marker for insulin resistant. Increasing the level of adiponectin prevent the progression of insulin resistant (IR). In this research we are striving adiponectin as a biomarker for insulin resistant also associating the correlation with lipid parameter in the South Indian population. Methods: 30 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…On the other hand, research has shown that a low level of adiponectin, a peptide produced by adipose tissue (Banu & Elango, 2019), is associated with the prevalence of metabolic syndrome (Banu & Elango, 2019; Mohammad Rahimi et al, 2020), insulin resistance (Adiyaman et al, 2020), coronary heart disease (Lindberg et al, 2017), and diseases related to inflammation (Mohammad Rahimi et al, 2022). Elevated levels of adiponectin promote insulin sensitivity in skeletal muscles by binding to adiponectin receptor type 1 and 2, which triggers the activation of several signaling pathways (Roy & Palaniyandi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, research has shown that a low level of adiponectin, a peptide produced by adipose tissue (Banu & Elango, 2019), is associated with the prevalence of metabolic syndrome (Banu & Elango, 2019; Mohammad Rahimi et al, 2020), insulin resistance (Adiyaman et al, 2020), coronary heart disease (Lindberg et al, 2017), and diseases related to inflammation (Mohammad Rahimi et al, 2022). Elevated levels of adiponectin promote insulin sensitivity in skeletal muscles by binding to adiponectin receptor type 1 and 2, which triggers the activation of several signaling pathways (Roy & Palaniyandi, 2021).…”
Section: Introductionmentioning
confidence: 99%